18 gold, 12 silver in ITEX - Nur Laila, Afandi (2018)
Kuala Lumpur, 12 May – Universiti Malaysia Pahang (UMP) was awarded Patron of ITEX Award for its outstanding achievement with 18 gold and 12 silver medals in 29th International Invention & Innovation Exhibition (ITEX) that was held at Kuala Lumpur Convention Centre recently.